Sistem Pendukung Keputusan Pemilihan Siswa Terbaik Menggunakan Metode Multi-Attribute Utility Theory (MAUT): SD Islam Nurul Mubin NW Iwan Bongkot - Saikin Saikin; Sofiansyah Fadli; Hairul Fahmi (STIKes Ibnu Sina Ajibarang, 2025)
Selection Optimal student selection can involve many considerations. The challenges faced in optimal student selection include the establishment of criteria that are explicit and objective criteria, accessibility of appropriate data to evaluate the student performance and qualifications, and ambiguity or disagreement surrounding the decisions made. This research aims to apply the Multi-Attribute Utility Theory Theory of Multi-Attribute Utility (MAUT) for the selection of exemplary students, thus facilitating the process for educational institutions, particularly student affairs departments, to identify the best students at the end of each semester. Results ranking showed that the first position was achieved by the student M. Qinan Hasan Al-Gazy with a final score of 0.65, the second position was achieved by student Rifqi Saputra with a final score of 0.62, the third position was achieved by student A. Gifari Pratama with a final score of 0.4854, and the fourth position was achieved by student Muh. Alfian with a final score of 0.25.